2015
DOI: 10.21608/asnj.2015.59779
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Educational Program about Cancer Pain Management on Nurses' Knowledge, Attitudes, and Practice at Intensive Care Unit

Abstract: Background: cancer pain has emerged as a leading stressor for patients with cancer in the intensive care unit (ICU).Unrelieved pain gives rise to negative physiologic and psychological events that can be detrimental to critically ill patients" health outcomes Aim of the study: evaluate the impact of an educational program about cancer pain management on nurses' knowledge, attitudes and practice at intensive care unit. Subject and methods: Quasi-experimental design was utilized in this study. A convenience samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…In relation to sex, in the present study it was found that (87.5%) were females and (12.5%) of them were males .This is in line with Musleh Band et al 2015 (60) , who reported that (87.3%) of the studied nurses were females and 12.7% were males. This is with disagreement with Sharour L 2018 (61) who report that 61.8 % were males and 47.3 %were females, and also rejected by El-AqoulA and et al A 2020 (62 ) , who reported that 60.3 % were males and 39.7% were females.…”
Section: Table (2) Showed Percent Distribution Of Levels and Mean Sco...supporting
confidence: 90%
“…In relation to sex, in the present study it was found that (87.5%) were females and (12.5%) of them were males .This is in line with Musleh Band et al 2015 (60) , who reported that (87.3%) of the studied nurses were females and 12.7% were males. This is with disagreement with Sharour L 2018 (61) who report that 61.8 % were males and 47.3 %were females, and also rejected by El-AqoulA and et al A 2020 (62 ) , who reported that 60.3 % were males and 39.7% were females.…”
Section: Table (2) Showed Percent Distribution Of Levels and Mean Sco...supporting
confidence: 90%